Pengembangan Mobile Learning Berbasis Android (Studi Kasus pada Mata KuliahAnalisisPerancanganSistem) - Afdhil Hafid; Efrizon Efrizon; Muhammad Adri (Universitas Negeri Padang, 2014)
Indonesian society more 'technological literacy' at the moment, along with a high need for information and supported by sophisticated IT devices like PCs, gadgets or smartphones. IT devices not only use by business environment but also at education. People who really need the information today would make the smartphone cannot be separated from day life. This makes students want a mobile device can be present in a class. In education environment it is known as mobile learning.It can also be a solution to the limitation of resources in education in order to access learning materials anywhere, anytime.Design Instructional is used to build applications, including construction and structure of teaching materials in a ‘mind map’ that will be given to students. Content provided in m-learning include the material in the form of text, images and simulation quiz. The application of mobile learning in the Android smartphone application form can be mobile learning systems integrated. Applications are made in an environment of learning Android using the Eclipse IDE for Jav.,Simulations quiz can also be applied to mobile applications in order to improve the understanding and the quality of learning. Selected engineering system development is the Waterfall model. Object-oriented design using UML modeling tools (Unified Modeling Language). The creation of mobile learning applications based on Android subjects Design Analysis Systems .At last, the creation of mobile learning applications based on Android subjects Design Analysis System can be m-learning resources based on Android system design analysis courses on informatics engineering education courses. It also can support class learning by using applications. Keywords: android, app, education,eclipse, information, interactive, java, mobile learning, platforms, resources, smartphones, technology, text.